Age and sex patterns of mortality in a tertiary care teaching hospital in Bagalkot, North Karnataka, India - Shankar, Gowri; Kalburgi, Eshwar B. (International Journal Of Community Medicine And Public Health, 2020)
Background: Mortality is an inevitable component of hospital practice and patient outcomes. The age and cause of death and sex mortality pattern and the audit give a myriad of information. This helps to identify the trend of mortality. Hence, this study was done to identify age and sex patterns of mortality of the patients admitted to Hangal Sri Kumareshwar Hospital and Research Centre, Navanagar, Bagalkot, Karnataka, India. Methods: A retrospective study of all deaths that occurred in the year 2018 in Hangal Sri Kumareshwar hospital and Research Centre, Navanagar, Bagalkot, Karnataka was done by analysing the records from medical records department after institutional review board clearance. Data regarding age, sex, area of residence, ward of admission and cause of death was noted and analysed using percentages and chi square test. Results: Out of 411 deaths during 2018 in HSK hospital, 64.96% were males and 35.04% were females. Majority (71.53%) were from rural areas. Maximum number of deaths (27.98%) was observed in those more than 61 years of age followed by those between 41 to 60 years of age. Overall, maximum number of deaths (69.35%) was due to a Non communicable disease. Infectious and parasitic disease contributed to 10.46% of deaths. Cardio vascular disease contributed to 16.30% deaths. Conclusions: Primary prevention of non-communicable diseases by creating awareness in the community and secondary prevention by early identification is needed to prevent premature mortality before the age of 60 years.